2007
DOI: 10.1039/b618045k
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of crosslinked chitosan/poly(vinyl alcohol) blend beads with high mechanical strength

Abstract: Crosslinked chitosan beads reported in the literature have the disadvantage of high water content and thus low mechanical strength. In this paper, a chitosan/poly(vinyl alcohol) (PVA) blend aqueous solution was first suspended in toluene-chlorobenzene to form droplets. Some of the water was then distilled out as an azeotrope with the aromatic hydrocarbons to reduce the water content of the suspension droplets. Glutaraldehyde was finally added to the suspension to result in the crosslinked chitosan/PVA beads wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 28 publications
0
34
0
Order By: Relevance
“…In addition, the mechanical intensities of the microspheres were better, and could be enhanced by cross-linking with cross-linking agent (e.g. glutaraldehyde, epichlorohydrin, ethylene glycol glycidyl ether, etc) [49] to expand its applications at higher pressure.…”
Section: Physical Properties Of the Cellulose Microspheresmentioning
confidence: 98%
“…In addition, the mechanical intensities of the microspheres were better, and could be enhanced by cross-linking with cross-linking agent (e.g. glutaraldehyde, epichlorohydrin, ethylene glycol glycidyl ether, etc) [49] to expand its applications at higher pressure.…”
Section: Physical Properties Of the Cellulose Microspheresmentioning
confidence: 98%
“…They were then soaked in acetate buffer maintained at 4°C and again weighed, following removal of excess buffer with filter paper, after 18 h (W s ). The swelling ratio was determined according to [33,34]:…”
Section: Swelling Ratiomentioning
confidence: 99%
“…Chabba et al crosslinked soy flour/flax yarns composites using glutaraldehyde (GA) as the crosslinking agent to improve the tensile and thermal properties [19]. Li et al also used GA to prepare crosslinked chitosan/PVA blend beads with high mechanical strength [20]. Teramoto et al reported that the miscibility and mechanical properties of pullulan/PVA composites were significantly improved after being crosslinked with glyoxal [21].…”
Section: Introductionmentioning
confidence: 98%